Evaluation of early resin luting cement damage induced by voids around a circular fiber post in a root canal treated premolar by integrating micro-CT, finite element analysis and fatigue testing. Issue 7 (July 2018) - Chang, Yen-Hsiang; Wang, Hsuan-Wen; Lin, Pei-Hsun; Lin, Chun-Li
Highlights: Integrating micro-CT, FE analysis and fatigue testing to investigate luting cement early damage. Voids occurred in the apical fiber post root and the surrounding regions. Voids induced the stress concentration of the luting cement adjacent to the apical third of the fiber post. Fatigue life was found decreased with the stress value/micro-motion increasing. Attention must be paid to luting cement dissolving/debonding easier when voids occurred. Abstract: Objective: This study utilizes micro-CT image combined with finite element (FE) analysis and in vitro fatigue testing to investigate the mechanical behavior associating with early resin luting cement damage induced by voids around a circular fiber post in a root canal treated premolar. Methods: Six similar mandibular first premolars with root canal treatment were scanned with high resolution micro-CT before and after fatigue testing. Micro-CT images of all teeth were processed to identify various materials (dentin, luting cement and void) to evaluate the volume/position of the void in each reconstructed tooth root canal model. Six corresponding mesh models from CT images were generated to perform FE simulations under receiving oblique concentrated loads (200 N) to evaluate the luting cement layer mechanical behavior. All teeth were subjected to the fatigue test with 240, 000 load cycles simulating chewing for one year to compare results with those in FE simulations. Results: The result showed that most voids occurred adjacent to the apical third of the fiber post. Voids induced the fiber post to pull out, creating a stress concentration at the void boundary. Fatigue life in the experimental testing was found decreased with the stress value/micro-motion increasing in FE analysis. Significance: This study establishes that micro-CT, FE simulation and fatigue testing can be integrated to understand the early de-bonding mechanism at the luting cement layer in a root canal treated premolar, suggesting that attention must be paid to resin luting cement dissolving/debonding easier when voids occur in the apical and peri-apical areas of fiber posts.